Opportunities in the digital world - Jakab, Natália (Autonomy and Responsibility Journal of Educational Sciences, 2022)
At Gandhi High School, the first steps towards digital education were not taken due to the shutdown caused by the Crown virus, but there is no doubt that this situation has accelerated the process in the life of the institution. At the time, we did not know how significant this would be. Our aim is not only to reduce digital disadvantage, but also to learn how to use the tools effectively to help students find employment. More than 80% of our students come from small, disadvantaged and disadvantaged communities. disadvantaged regions, so it was particularly important to consider the possible introduction of digital education that may be introduced. In addition to student surveys (device, internet, learning learning environment), it was also important for us to be able to stay in constant, daily contact with our students to avoid any drop-outs. This paper is about the digital school The aim of this paper is to explore the difficulties and achievements of the digital school.